2023
DOI: 10.1186/s40561-023-00229-x
|View full text |Cite
|
Sign up to set email alerts
|

Active learning and education 4.0 for complex thinking training: analysis of two case studies in open education

Abstract: This article focuses on empirically analyzing the final products designed by 147 academics from 11 countries who participated in an international open education movement workshop by answering the research questions “What are the techno-pedagogical components of the products designed by the participants to encourage the open educational movement? and what practice of the open educational movement is being executed?” The article starts with a conceptual basis that describes the concepts of Active learning, Educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 54 publications
0
14
0
2
Order By: Relevance
“…Students find value in team-based interactions, quizzes, and other collaborative tasks that require them to actively apply their knowledge and engage with peers. This collaborative approach aligns with the principles of active learning, which emphasize hands-on, studentcentered approaches to enhance learning (Patiño et al, 2023). These interactions stimulate critical thinking and foster a deeper understanding of the subject matter.…”
Section: Keyword: Effort and Persistencementioning
confidence: 76%
“…Students find value in team-based interactions, quizzes, and other collaborative tasks that require them to actively apply their knowledge and engage with peers. This collaborative approach aligns with the principles of active learning, which emphasize hands-on, studentcentered approaches to enhance learning (Patiño et al, 2023). These interactions stimulate critical thinking and foster a deeper understanding of the subject matter.…”
Section: Keyword: Effort and Persistencementioning
confidence: 76%
“…Learners appreciated the clear, evidence-informed, and up-to-date information in the modules which they thought addressed gaps in their current curricula. Learners also indicated that curricular elements including use of case-studies (20,21) which covered diverse lived experiences helped them to see how the content would be applicable to their future practice. Case studies are viewed as important learning strategies and with the recent technological advances (e.g., ChatGPT) they can further support individualizing the case studies to speci c learner needs and continue to promote self-regulated and self-directed learning opportunities (22).…”
Section: Discussionmentioning
confidence: 99%
“…Complex thinking emerges as a valuable tool in future education (Ramı ´rez-Montoya et al, 2024b), giving rise to research that serves as guiding frameworks for cultivating skills through innovative educational strategies such as competency-based, problem-based and casebased learning and gamification (Cruz-Sandoval et al, 2023). These studies suggest that conventional strategies, bolstered by the use of technological tools such as reading, debates and reflective questions, remain effective in fostering complex thinking when applied appropriately (Patin ˜o et al, 2023). In the effort to enhance educational methods and adapt to an ever-changing environment, complex thinking emerges as an essential tool.…”
Section: Complex Thinking In Higher Educationmentioning
confidence: 99%
“…, 2023). These studies suggest that conventional strategies, bolstered by the use of technological tools such as reading, debates and reflective questions, remain effective in fostering complex thinking when applied appropriately (Patiño et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%